Perspective and circumstance in making decisions:The 4D model of the world of enterprise - Acevedo Borrego, Adolfo Oswaldo (2011)
To understand and solve business problems, the decision maker has a basic orientation to any dimensión of the organization. The 4 dimensións model is based on the perspective to understand and manipulate the business world: technical perspective that manages things and human perspective that is responsible for directing people to the task and performance, integration of both perspectives defines the basic preference of decision maker. The circumstance, that represents the problematic situation, alters this perception and restricts the options of choice. So the understanding of issues is related to the preference of decision maker and its solving is influenced by environmental pressures. This study attempts to show the effect of circumstance on the decision maker’s preference. The basic orientation of decision makers is varied and does not follow a particular pattern, but given the pressures of the competitive environment, managers are focused on the visible results, measured in productivity and efficiency, considering stability criteria and risk reduction or effects not expected. The management of decisional guidance facilitates the anticipation of problems and developing strategies for trading in competitive or cooperative groups.